New reduction of old glass astronomical plates of Pallas and Vesta in 1956–1994 based on Gaia DR3 catalogue. (March 2023) - Wang, L.L.; Yu, Y.; Yuldoshev, Q.X.; Ehgamberdiev, Sh.A.; Shang, Z.J.; Yang, M.T.; Yang, J.; Dong, S.; Da, D.M.; Tang, Z.H.; Zhao, J.H.; Muminov, M.M.
Abstract: Through a key project for intergovernmental international cooperation between Uzbekistan and China, a group of old glass astronomical plates of Pallas and Vesta taken by the TAS033 telescope at Tashkent observation site of Ulugh Beg Astronomical Institute in 1956–1994 have been digitized using the digitizer with sub-micrometer measuring precision newly developed by Shanghai Astronomical Observatory. Based on the Gaia DR3 catalogue, a new reduction of these old observations was carried out. A total of 105 Pallas and 83 Vesta astrometric positions were derived. The comparison with theoretical values from JPL ephemerides indicates that the dispersion of the positions of Pallas from the digitized plates are better than 0.13″ in both right ascension and declination, and the dispersions of the positions of Vesta are better than 0.21″. Highlights: Observations made on a long time-span are necessary to study the dynamics of Solar System bodies. A group of old plates of Pallas and Vesta taken in 1956–1994 were digitized and reduced based on Gaia DR3. A total of 105 Pallas and 83 Vesta astrometric positions were derived. The precision of the new reduction from these old plates is 0.1″–0.2″.